El deber de motivación. Una exigencia del neoconstitucionalismo para la aplicación y creación del derecho (2009)
This article set out that in constitutional law tensions are present in the application and interpretation of rights included in the Constitution, and debate arise about the way courts and judges have try to solve those tensions. Summarizes a first jurisprudential approximation about the duty of motivation ofthe decisions –administrative and judiciaries– and its conceptualization, according to criteria given by the Colombian Constitutional Court.